Risk of diabetes mellitus in physicians: a nationwide study in Taiwan - Shang-Gyu Lee; I-Jung Feng; Chien-Chin Hsu; Yi-Fong Wang; Chewn-Yi Yang; Jhi-Joung Wang; Jui-Yuan Chung; Chien-Cheng Huang (BMC, 2019)
Abstract Background The heavy workload of physicians in Taiwan may contribute to poor lifestyles and increased risk for diabetes mellitus (DM). We conducted this study to determine the risk for DM among physicians in Taiwan. Methods We used the Taiwan National Health Insurance Research Database to identify 28,440 physicians and 56,880 comparisons (general population) matched at a ratio of 1:2 by age and sex. Participants who had been diagnosed with DM before 2007 were excluded. We compared the risk for DM between physicians and comparisons by following up since 2007 to 2013. Comparisons among physician subgroups were also performed. Results After adjustment for hypertension, hyperlipidemia, hyperuricemia, coronary artery disease, congestive heart failure, hyperthyroidism, hypothyroidism, and polycystic ovary syndrome, physicians had a lower risk for DM than the comparisons (adjusted odds ratio [AOR]: 0.75; 95% confidence interval [CI]: 0.68-0.82). In comparisons among physicians, emergency physicians (AOR: 2.21; 95% CI: 1.44-3.40) and surgeons (AOR: 1.26; 95% CI: 1.05-1.52) had a higher risk for DM than other specialists. Conclusions This study found that physicians have a lower risk for DM than the general population and emergency physicians and surgeons have a higher risk for DM than other specialists. Thus, more attention should be paid to the occupational health of these doctors.